A Green and Simple Protocol for Extraction and Application of a Peroxidase-Rich Enzymatic Extract - Rosa, Gonçalo P. (2021)
Recently there is a great social expectation that scientists should produce more sustainable and environmentally friendly chemical processes. Within this necessity, biocatalysis presents many attractive features because reactions are often performed in water, under mild conditions, the catalyst is biodegradable and can be obtained from renewable raw materials. In this work, we propose a simple, rapid and low-cost method for the preparation and application of an enzymatic extract from turnip root. The protocol described includes (1) the preparation of the enzymatic extract, (2) the procedure for the assessment of the more favorable working parameters (temperature, pH) and (3) the methodology for the application of the extract as the catalyst for biotransformation reactions. We anticipate that the protocol in this research will provide a simple way for obtaining an enzymatic extract which can operate efficiently under mild conditions and can effectively catalyze the biotransformation of simple phenols.